Utilization of PET Plastic Waste in Concrete Asphalt Mixture (AC-BC) to Improve the Stability and Sustainability of Road Infrastructure - Andri Dwi Cahyono; Zendy Bima Mahardana; Evita Fitrianis Hidiyati; M. Faisol Firmansyah; Erwindsyah Putra W (Universitas Negeri Padang, 2025)
Plastic waste, especially Polyethylene Terephthalate (PET), is one of the biggest environmental issues in Kediri City, with a volume of 140 tons per month. This research aims to utilize PET plastic waste as an additional material in the Asphalt Concrete-Binder Course (AC-BC) mixture. The study was conducted using an experimental method with variations in PET levels of 0%, 6%, 8%, and 14% of the total weight of the mixture. The test was carried out using Marshall standards to evaluate performance parameters such as stability, flow, VIM (Void in Mix), VMA (Void in Mineral Aggregate), and VFB (Void Filled with Bitumen). The results showed that the addition of PET to 6% increased the stability of the mixture to 6300 kg, higher than the mixture without PET (6200 kg). The flow value increased with the addition of PET, reaching 3.8 mm at a rate of 14%. In addition, VMA and VIM tend to decrease, indicating an increase in the density of the mixture, while VFB achieves an optimal value at a PET level of 6%. This study concluded that PET waste can be used effectively to improve the performance of AC-BC mixtures, with an optimal level of 6%. The utilization of PET plastic waste not only improves the performance of road infrastructure but also contributes to the reduction of plastic waste, thus supporting environmentally friendly and sustainable construction solutions.